PTX3 mediates PI3K/AKT/mTOR signaling to downregulate apoptosis and autophagy to attenuate myocardial injury in sepsis - Cui,Na; Chen,Zhi; Yu,Zhanbiao; Lv,Xiaowei; Hu,Zhenjie (PeerJ, 2024)
Background This study aimed to investigate the effect and mechanism of Pentraxin 3 (PTX3) on myocardial injury in sepsis. Methods Thirty male C57BL/6 mice were randomly assigned to Groups A, B, or C. Mice in Groups A and B were injected with unloaded lentivirus, while mice in Group C were injected with lentivirus encoding PTX3 overexpression. Seven days after injection, septic myocardial injury mouse models were constructed following intraperitoneal injection with LPS in Groups B and C, and mice in Group A were intraperitoneally injected with normal saline. Cardiac function was examined using echocardiography; pathological variation of myocardial cells was measured through HE staining, transmission electron microscopy, and TUNEL staining; and Western blot was used to measure the expression of PI3K/AKT/mTOR pathway-related, autophagy-related, and apoptosis-related proteins in mice myocardial cells. Results PTX3 significantly improved cardiac function and structure in sepsis-stricken mice, and PTX3 alleviated cardiac damage caused by sepsis. PTX3 reduced the relative protein expression of p-PI3K, p-AKT, mTOR, LC3I/II, Beclin, ATG5, Bax, Caspase-3, and Caspase-9 in septic mouse cardiomyocytes and increased the relative protein expression of Bcl-2. Conclusion PTX3 can attenuate myocardial injury in sepsis due to the down-regulation of apoptosis and autophagy induced by the PI3K/AKT/mTOR pathway.
Keywords: PTX3; Myocardial injury; Apoptosis; Autophagy